PERAN GURU DALAM MENGEMBANGKAN KREATIVITAS ANAK USIA DINI - AISYAH AISYAH; Aulia Insani (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2021)
Each child has a variety of different abilities, and talents brought from birth. In the hands of intelligent and barrel teachers, children can grow into people who think, spirit, and work big. But with a variety of different abilities it needs to be done various ways to develop these abilities. One of these abilities is creativity. Creativity is not an innate ability from birth, but an ability that can be learned and developed. Creativity is important to develop because creativity affects a person's life. With creativity one is driven to create new ideas, discoveries or technologies that can improve the well-being of society at large. With their creativity, they can become creative individuals. So that this ability can be developed early on.